Decision-Making Analysis on The Credit Card Partnership Program Using Kepner-Tregoe and Smart Technique Approaches - Rafly Aqsha Gultom; Manahan Parlindungan Sarigih Siallagan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study analyzes the root causes of underperformance in PT Bank XYZ’s credit card partnership program with F&B merchants. Using the Kepner-Tregoe (KT) Problem Solving Framework and the SMART (Simple Multi-Attribute Rating Technique), the research adopts an exploratory-descriptive qualitative approach involving Forum Group Discussions (FGDs) with internal stakeholders. The analysis identified two main problems: weak internal coordination between the EDC and Marketing teams, and low merchant and cashier engagement in executing promotional programs. Three alternative solutions were evaluated: (1) Integrated Merchant Engagement Program, (2) Internal KPI Synchronization Framework, and (3) Real-Time Performance Dashboard. The SMART evaluation determined the first alternative as the most effective, with the highest score (4.3), based on impact, feasibility, and ROI. The solution includes digital training, promotional kits, and incentive systems to enhance cashier performance. Supporting frameworks and monitoring systems were also proposed to ensure sustainable impact. The findings emphasize the importance of data-driven decision making, internal alignment, and proactive merchant involvement to enhance the success of banking partnership programs. This study contributes to strategic decision-making literature in the financial services sector by demonstrating the effective integration of KT and SMART to resolve operational inefficiencies. Keywords: Kepner-Tregoe, SMART Technique, Credit Card Partnership, Decision Analysis, Banking Strategy